Salinity tolerance and desalination properties of a Haematococcus lacustris strain from eastern Hungary - Bácsi, István; Figler, Aida; Simon, Edina; Yaqoob, Majd Muwafaq; Márton, Kamilla; B-Béres, Viktória (Frontiers in Microbiology, 2024)
Nowadays the increasing amount of saline wastewaters has given rise to various biological desalination processes, among which the application possibilities of microalgae represents a priority research area. Next to "real" aquatic species (members of phytoplankton or phytobenthon), species from ephemeral aquatic habitats or aeroterrestrial algae also could be good candidates of research studying salt tolerance or desalination ability, since salinity stress is often referred as "physiological drought" and species from ephemeral habitats can be characterized by high drought tolerance. In this study, the salinity tolerance, salt and nutrient removal ability of a Haematococcus lacustris strain from eastern Hungary were investigated. Vegetative cells showed low salt tolerance, survival was ensured by the formation of cysts up to a sodium-chloride concentration of 2,000 mg l -1 . Although relatively moderate (a max. 30%) conductivity reduction and chloride removal were observed, notable (nearly 100%) nitrate and phosphate removal occurred even in the presence of 2,000 mg l -1 NaCl. Carotenoid accumulation was observed earlier and in higher extent in salt treated cultures than in drying out ones, although the amount of astaxanthin-esters was significantly higher in the cultures of drying out experiment than in the corresponding cultures of salt treatment characterized with similar chloride content. Our results suggest that algae isolates from ephemeral aquatic habitats endangered by regular drying out (exposed to special salt stress), could have notable salt tolerance and consequently successful applicability in nutrient removal processes from slightly saline